On designing OTA-C graphic-equalizers with MOSFET-triode transconductors - De Lima, J. A. [UNESP]; Petraglia, A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2001)
A CMOS audio-equalizer based on a parallel-array of 2nd-order bandpass-sections is presented and realized with triode transconductors. It has a programmable 12db-boost/cut on each of its three decade-bands, easily achieved through the linear dependence of gm on VDS. In accordance with a 0.8μm n-well double-metal fabrication process, a range of simulations supports theoretical analysis and circuit performance at different boost/cut scenarios. For VDD=3.3V, fullboosting stand-by prover consumption is 1.05mW. THD=-42.61dB@1Vpp and may be improved by balanced structures. Thermal- and I/f-noise spectral densities are 3.2μV/Hz12 and 18.2μV/Hz12@20Hz, respectively, for a dynamic range of 52.3dB@1Vpp. The equalizer effective area is 2.4mm2. The drawback of the existing transmission-zero due to the feedthrough-capacitance of a triode input-device is also addressed. The proposed topology can be extended to the design of more complex graphic-equalizers and hearing-aids.
Keywords: Bandpass filters; Electric converters; Energy utilization; MOSFET devices; Spectrum analysis; Thermal noise; Transconductance; Graphic equalizers; Transconductors; Decision feedback equalizers